Role of Cytokines and Chemokines in the Outcome of Children With Severe Asthma - Hamed Hatami; Negar Ghaffari; Javad Ghaffari; Houshang Rafatpanah (Mazandaran University of Medical Sciences, 2019)
Context: Asthma, characterized by airway inflammation, is a common chronic disease of childhood. Cytokines and chemokines could be used in the diagnosis, treatment, and management of asthma severity in children. In this review, we have explained the application of cytokines and chemokines as biomarkers in pediatric asthma. Evidence Acquisition: All related articles were separately searched by two researchers using the following keywords in PubMed, Scopus, and Embase databases: Cytokine biomarkers, chemokines biomarkers, and children asthma. Articles published from 2000 to 2017 were investigated in the research, and 28 articles were included in the final analysis for this review. Results: About cytokines, serum Interleukin 4 (IL-4) level is a marker of the presence of asthma, and IL-13 is a key cytokine involved in the manifestation of asthma symptoms. High IL-13 concentration and number of IL-13+ cells in the bronchial submucosa specimens are characteristic of severe asthma. Serum IL-5 concentration 3.1 times in children with severe asthma. IL-17 is involved in airway obstruction. IFN-γ gene polymorphism (+874A/T) in children elevates susceptibility to asthma. TGFB1 polymorphisms are considered as indicators of asthma severity. IL-26 plays an important role in asthma severity. IP-10 may be a useful inflammatory marker of asthma severity. High periostin level has been identified in pediatric asthma. PDGF level, which is high in asthma patients, plays an important role in bronchial fibrosis. About chemokines, plasma TARC concentration may be a useful biomarker of airway inflammation and asthma severity in children. Studies have supported the association between high serum RANTES levels and severe airway obstruction in children. CXCR4 levels are high in pediatric asthma and are associated with disease severity. Conclusions: A wide range of cytokines and chemokines may play important roles in asthma severity in pediatric patients. Therefore, several studies have recommended the use of multiple molecular biomarkers, such as cytokines, for determining asthma severity in children.